2008
DOI: 10.1111/j.1467-9523.2008.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Work in Norwegian Family Farm Businesses

Abstract: The traditional way of organising agricultural production in Norway has been through family farming. A family farm is defined by the ownership of the farm through kinship over a number of generations. This article examines structural changes on Norwegian family farms based on the impact of increased competition and falling prices and subsidies. The strategy traditionally employed has been to increase total household income on the farm through working off-farm. We map changes in income allocation and work strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 11 publications
(21 reference statements)
3
28
0
2
Order By: Relevance
“…The aims were full-time farming and getting rid of pluriactivity, but this never fully succeeded (Jones and Rønningen, 2007). Bjørkhaug and Blekesaune (2008) observed the strong trend towards increasing off-farm work by farmers and farm women, to the extent that two thirds of net farm household income from farmer and spouse was off-farm income in 2003 (Bjørkhaug and Blekesaune, 2008;Statistics Norway, 2009a). Today, only 21% of farms have no registered income from outside agriculture (Logstein, 2010).…”
Section: Historical and Geographical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The aims were full-time farming and getting rid of pluriactivity, but this never fully succeeded (Jones and Rønningen, 2007). Bjørkhaug and Blekesaune (2008) observed the strong trend towards increasing off-farm work by farmers and farm women, to the extent that two thirds of net farm household income from farmer and spouse was off-farm income in 2003 (Bjørkhaug and Blekesaune, 2008;Statistics Norway, 2009a). Today, only 21% of farms have no registered income from outside agriculture (Logstein, 2010).…”
Section: Historical and Geographical Contextmentioning
confidence: 99%
“…Critics also claim that the allodial principle prevents innovation and adaptation to a changing world (Aanesland and Holm, 2002). On the other hand, since allodial law was amended in 1975 it has encouraged daughters to take over farms (Bjørkhaug and Blekesaune, 2008), and this is seen as an important contribution to gender equality and recruitment of young women to rural areas. Price controls are also criticised on the grounds that the regulated price reduces incentives to sell.…”
Section: Agricultural or Rural Policy E Or Mountain Policy? The Mountmentioning
confidence: 99%
“…Wage income from off-farm work has exceeded farm income on the average Norwegian farm since the 1980's (Jervell and Løyland, 1998). During the same period, the average working hours on Norwegian farms increased (Bjørkhaug & Blekesaune, 2008). This decreasing value of farm work occurred due to changes in agricultural subsidies and commodity prices, but also as a result of more women working longer hours off the farm.…”
Section: The Continuing Domination Of the Family Farmmentioning
confidence: 99%
“…Several studies later showed how part-time farming has developed as a sustainable format of structural adjustment over time (e.g. Bjørkhaug & Blekesaune, 2008;Blekesaune, 1996a). It has been not been shown that part-time farming replaces family farming due to definitional differences, but rather that family farming currently is dependent on off-farm income, as is the continuation of family farming in Norway.…”
Section: Theorising Sociology Of Agriculturementioning
confidence: 99%
“…However, some characteristics seem to apply to most migrant workers in the Norwegian agricultural sector. Firstly, Norwegian agricultural production is typified by its small scale and family farming, combined with very strong state regulation (Bjørkhaug and Blekesaune 2008). Farms are dispersed across the country, with farmers living on their plots rather than agglomerated in villages.…”
Section: Analysis Part 1: Circularity Of Farm Work Migrationmentioning
confidence: 99%